2020
DOI: 10.21203/rs.3.rs-35018/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential role of serum angiotensin-converting enzyme in the coronavirus disease 2019

Abstract: Objective To explore the clinical significance of serum angiotensin-converting enzyme (ACE) in the coronavirus disease 2019 (COVID-19).Methods In this retrospective study, a cohort of 136 consecutive patients with confirmed COVID-19 was recruited. Demographics and clinical data were recorded. The serum ACE activity were measured at baseline and recovery phase, and its relationship with clinical condition was analyzed.Results Of the 136 patients with confirmed COVID-19, 16 severe cases were older, had higher bo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…5 Schematic outline of low serum ACE level in relation to inflammation, immune status, and clinical outcome normal level with disease remission. In that study, although the lowest ACE level was noted in the group with more severe infection, baseline ACE failed to serve as an independent risk factor for disease severity of COVID-19 [8]. To the best of our knowledge, this is the first investigation into whether, and to what extent, a relationship exists between ACE level and COVID-19 disease progression.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…5 Schematic outline of low serum ACE level in relation to inflammation, immune status, and clinical outcome normal level with disease remission. In that study, although the lowest ACE level was noted in the group with more severe infection, baseline ACE failed to serve as an independent risk factor for disease severity of COVID-19 [8]. To the best of our knowledge, this is the first investigation into whether, and to what extent, a relationship exists between ACE level and COVID-19 disease progression.…”
Section: Discussionmentioning
confidence: 80%
“…It has been indicated in recent years that serum ACE level correlates with the diagnosis and prognosis of a variety of respiratory disorders [7]; however, the potential relationship between ACE level and clinical outcomes of SARS-CoV-2 infection is not adequately understood. The latest research based on 136 patients with confirmed COVID-19 suggested that serum ACE level could serve as a marker to reflect the clinical condition of COVID-19 rather than an independent risk factor for disease severity [8]. In our study, 120 patients with confirmed COVID-19 who underwent measurement of serum ACE levels on admission were retrospectively enrolled, to evaluate the potential role of serum ACE level in combination with other risk factors in predicting disease progression of COVID-19 and further investigate the possible mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis that we carried out in the previous section has shed some light on these questions to a certain extent, but many points remain obscure. Indeed, the experimental and clinical data that we collected from the literature about e.g., the levels of proteins and peptides involved in RAS and the activity of the enzymes, partially disagree [77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92].…”
Section: Discussionmentioning
confidence: 99%
“…We review here recent data about measurements of RAS components in COVID-19. For that purpose, we manually collected and screened a series of clinical and experimental results from [77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92], listed in Supplementary Table S1. The individuals enrolled in these studies were classified into two or three classes: COVID-19 patients or severe and moderate COVID-19 patients, and controls or asymptomatic patients.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 99%
“…Immune-inflammatory disorders can be associated with ACE/ACE2 [41]. The role of ACE2 in SARS-CoV-2 infection stands itself as an irony.…”
Section: Angiotensin-converting Enzyme (Ace)-dependent Pathwaymentioning
confidence: 99%